1985
DOI: 10.1007/bf01786639
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in garden soils and vegetable crops in Cornwall, England: Implications for human health

Abstract: Total concentrations of arsenic in surface (0-15cm) garden soils in the historical mining area of Hayle-Camborne-Godolphin, Cornwall, England are large and range widely (144-892 μg/g). Amounts of water soluble and acid-fluoride extractable soil arsenic are significantly correlated with total content.Examination of 6 salad and vegetable crops grown in 32 gardens has shown arsenic concentrations in the edible tissues to be only slightly elevated. There were strong correlations between arsenic in beetroot, lettuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
3
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 6 publications
3
44
3
4
Order By: Relevance
“…These values are much higher than those reported in the studies of Kavanagh et al (1997) and Ganne et al (2006) in mine wastes and soils, but comparable with the studies of Xu, Thornton (1985) and Cao, Ma (2004). Arsenic contents associated with Fe and Mn oxides (18.67-935 mg kg -1 ) showed positive correlation with those of water soluble As (r 2 = 0.929, p < 0.001), suggesting that the Fe and Mn oxides are the source of the more mobile and bioavailable As in stream sediments and impoundment materials.…”
Section: Impoundmentsupporting
confidence: 85%
“…These values are much higher than those reported in the studies of Kavanagh et al (1997) and Ganne et al (2006) in mine wastes and soils, but comparable with the studies of Xu, Thornton (1985) and Cao, Ma (2004). Arsenic contents associated with Fe and Mn oxides (18.67-935 mg kg -1 ) showed positive correlation with those of water soluble As (r 2 = 0.929, p < 0.001), suggesting that the Fe and Mn oxides are the source of the more mobile and bioavailable As in stream sediments and impoundment materials.…”
Section: Impoundmentsupporting
confidence: 85%
“…In comparison with Xu and Thornton (1985) and Cao and Ma (2004), reporting maximum water-soluble As fractions of 2.78 and 3.02-13.6 % in garden soils in Cornwall and contaminated soils in the USA, respectively, the values obtained in the Dashkasan area were very low, probably due to the relatively low organic matter content.…”
Section: Arsenic In Soilmentioning
confidence: 62%
“…Often the condition of the soil is unknown or undocumented; therefore, exposure to toxic levels can occur. Xu and Thornton (1985) suggested that there are health risks from consuming vegetables with elevated heavy metal concentrations. The populations most affected by heavy metal toxicity are pregnant women or very young children (Boon and Soltanpour 1992).…”
mentioning
confidence: 99%